Modified lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof
The modified lithium manganese iron phosphate material, prepared through a surfactant-assisted method, addresses particle agglomeration issues by achieving nano-sized particles, improving lithium ion diffusion and electrochemical performance, and enhancing battery capacity and stability.
Patent Information
- Application Number
- CN202411502015.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-31
AI Technical Summary
The agglomeration of lithium manganese iron phosphate particles synthesized by ball milling methods leads to poor electrochemical performance, hindering its industrial application.
A modified lithium manganese iron phosphate positive electrode material is prepared by mixing a phosphoric acid source, manganese source, iron source, lithium source, carbon source, surfactant, and cosolvent, followed by ball-milling, vacuum-drying, and high-temperature sintering, using surfactants like oleic acid or quaternary ammonium salts to achieve nano-sized particles with improved morphology and electrochemical performance.
The solution addresses the agglomeration of lithium manganese iron phosphate particles, enhancing the electrochemical performance of the material by improving the diffusion efficiency of lithium ions and increasing the capacity and cycle stability of lithium-ion batteries.
Smart Images

Figure CN119230822A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode, and in particular to a modified lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, long cycle life, low self-discharge, and no memory effect. They are one of the most important electrochemical energy storage devices and have been widely used in portable electronic devices, electric vehicles, and large energy storage systems. They have become a research hotspot in the fields of new energy and new materials. The main cathode materials for lithium-ion batteries include lithium cobalt oxide, ternary materials, lithium manganese oxide, and polyanionic compounds with olivine structures (such as lithium iron phosphate). Among them, polyanionic compounds with olivine structures have the advantages of low cost, high theoretical specific capacity, good cycle stability and safety performance, and have attracted widespread attention from researchers. Mn is relatively cheap and abundant in resources compared to Fe, making it suitable for large-scale use. The biggest advantage of lithium manganese iron phosphate is its high operating voltage (up to 4.1V). Its theoretical energy density (701Wh / kg) is about 20% higher than that of lithium iron phosphate (586Wh / kg), and it is considered to be the material with the greatest potential to reach the maximum practical energy density platform.
[0003] The main synthesis methods of lithium manganese iron phosphate are divided into solid phase method and liquid phase method. The solid phase method has a simple preparation process and is suitable for large-scale industrial production. The solid phase method mainly includes high temperature solid phase method, ball milling method and rheological phase assisted solid phase method. However, the morphology of lithium manganese iron phosphate synthesized by ball milling method is seriously agglomerated, which has a serious impact on its electrochemical performance and hinders its industrial application. Summary of the invention
[0004] The purpose of the present invention is to provide a modified lithium iron manganese phosphate positive electrode material and a preparation method and application thereof to solve the problems existing in the above-mentioned prior art. The modified lithium iron manganese phosphate positive electrode material prepared by the present invention has significantly improved agglomeration of lithium iron manganese phosphate particles compared with the lithium iron manganese phosphate prepared without adding a surfactant, while increasing the capacity of the battery and having higher cycle stability and rate performance.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for preparing a modified lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0007] A phosphoric acid source, a manganese source, an iron source, a lithium source, a carbon source, a surfactant and a cosolvent are mixed, ball-milled, and vacuum-dried to obtain a lithium iron manganese phosphate precursor; the lithium iron manganese phosphate precursor is subjected to high-temperature sintering to obtain the modified lithium iron manganese phosphate positive electrode material;
[0008] The surfactant is oleic acid, hexadecyltrimethylammonium bromide or dodecyltrimethylammonium chloride.
[0009] Furthermore, the phosphate source is ammonium dihydrogen phosphate or diammonium hydrogen phosphate; the manganese source is manganese carbonate, manganese acetate, manganese phosphate, manganese trioxide or manganese tetraoxide; the lithium source is lithium acetate, lithium carbonate, lithium hydroxide or lithium chloride; the iron source is ferric phosphate, ferrous oxalate, ferric nitrate or ferric chloride.
[0010] Furthermore, the carbon source is citric acid, ascorbic acid, glucose, sucrose, polyethylene glycol or dopamine hydrochloride.
[0011] Furthermore, the molar ratio of the phosphate source, manganese source, iron source and lithium source is 1:1:1:1; the amount of the carbon source is 10% of the sum of the mass of the phosphate source, manganese source, iron source and lithium source.
[0012] Furthermore, the co-solvent is anhydrous ethanol and / or deionized water.
[0013] Furthermore, the usage ratio of the co-solvent to the phosphoric acid source is 40 ml:0.01 mol.
[0014] Furthermore, when the surfactant is oleic acid, the dosage ratio of the surfactant to the phosphoric acid source is 2 ml:0.01 mol; when the surfactant is hexadecyltrimethylammonium bromide or dodecyltrimethylammonium chloride, the dosage of the surfactant is 3% of the sum of the mass of the phosphoric acid source, manganese source, iron source and lithium source.
[0015] Furthermore, the rotation speed of the ball mill is 200 r / min, the ball-to-material ratio is 10:1, and the time is 10-20 h; the temperature of the high-temperature sintering is 600-750° C., and the time is 6-10 h.
[0016] Furthermore, the high temperature sintering is performed in an argon or nitrogen atmosphere.
[0017] The second technical solution of the present invention: a modified lithium manganese iron phosphate positive electrode material prepared by the above-mentioned preparation method.
[0018] Furthermore, the particle size of the modified lithium manganese iron phosphate positive electrode material is 50-200 nm.
[0019] Furthermore, the particle size of the modified lithium manganese iron phosphate positive electrode material is preferably 60-100 nm.
[0020] Furthermore, the modified lithium manganese iron phosphate positive electrode material is carbon-coated lithium manganese iron phosphate.
[0021] The third technical solution of the present invention: a lithium-ion battery positive electrode, comprising the above-mentioned modified lithium manganese iron phosphate positive electrode material.
[0022] Technical solution 4 of the present invention: The method for preparing the positive electrode of the lithium ion battery comprises the following steps:
[0023] The modified lithium manganese iron phosphate positive electrode material is mixed with conductive carbon black and a binder, and then NMP (N-methylpyrrolidone) is added for homogenization to obtain an active material coating; the active material coating is coated on a substrate, dried and then rolled to obtain the lithium ion battery positive electrode.
[0024] Furthermore, the binder is PVDF (polyvinylidene fluoride).
[0025] Furthermore, the mass ratio of the modified lithium manganese iron phosphate positive electrode material to the conductive carbon black and the binder is 80:10:10; the ratio of the added amount of the NMP to the sum of the mass of the modified lithium manganese iron phosphate positive electrode material to the conductive carbon black and the binder is 1-1.5 ml:1 g.
[0026] Furthermore, the substrate is an aluminum foil.
[0027] Furthermore, the coating thickness of the active substance coating on the substrate is 10-20 μm.
[0028] Furthermore, the drying temperature is 80°C.
[0029] The fifth technical solution of the present invention: a lithium ion battery, using the above-mentioned lithium ion battery positive electrode as the positive electrode.
[0030] The lithium-ion battery is a button-type half-cell, comprising a negative electrode shell, a lithium sheet, an electrolyte, a diaphragm, an electrolyte, a positive electrode sheet, a gasket, a spring and a positive electrode shell.
[0031] The present invention discloses the following technical effects:
[0032] (1) Compared with the prior art, the method for preparing lithium iron manganese phosphate positive electrode material by surfactant modification in the present invention can achieve nano-sizing of lithium iron manganese phosphate, improve the agglomeration of lithium iron manganese phosphate particles, reduce the particle size of lithium iron manganese phosphate, thereby shortening the diffusion distance of lithium ions, improving the diffusion efficiency of lithium ions, and enhancing the electrochemical performance of the material.
[0033] (2) The method for preparing the lithium iron manganese phosphate positive electrode material of the present invention is simple in process, convenient in operation flow, easy in process control, low in cost, and easy in industrial large-scale production. Compared with the existing lithium iron phosphate and ternary materials, the lithium iron manganese phosphate positive electrode material prepared by the present invention has a higher voltage platform. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is the XRD pattern of the modified lithium iron manganese phosphate prepared in Example 1 of the present invention;
[0036] Figure 2 This is a SEM image of lithium manganese iron phosphate (without adding surfactant) prepared in Comparative Example 1 of the present invention;
[0037] Figure 3 This is a SEM image of the modified lithium iron manganese phosphate prepared in Example 1 of the present invention;
[0038] Figure 4 This is a surface scanning energy spectrum of the modified lithium manganese iron phosphate obtained in Example 1 of the present invention;
[0039] Figure 5 This is a charge and discharge curve diagram of a battery prepared by using the modified lithium manganese iron phosphate of Example 1 at room temperature and 0.1C current;
[0040] Figure 6 This is a cycle stability diagram of a battery prepared using the modified lithium manganese iron phosphate of Example 1 at room temperature and 0.1C current. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] All raw materials used in the specific implementation of the present invention are common commercial products.
[0047] Example 1
[0048] A method for preparing a modified lithium manganese iron phosphate positive electrode material, the steps are as follows:
[0049] First, 40ml of anhydrous ethanol and 2ml of oleic acid were added to the ball mill, and then 0.01mmol of diammonium hydrogen phosphate, 0.01mmol of lithium carbonate, 0.01mmol of manganese carbonate and 0.01mmol of ferrous oxalate were weighed, and then 10% of the total mass of diammonium hydrogen phosphate, lithium carbonate, manganese carbonate and ferrous oxalate was weighed as a carbon source. All the above solid raw materials were evenly ground in a mortar and added to the ball mill, and ball milled for 15h (the ball mill speed was 200r / min, and the ball-to-material ratio was 10:1), and then washed with anhydrous ethanol 3 times, and vacuum dried (80℃ dried for 2h) to obtain a yellow lithium iron manganese phosphate precursor. Then the lithium iron manganese phosphate precursor was placed in a quartz crucible and sintered at high temperature under the protection of a nitrogen atmosphere. The sintering cycle was 6h, and the insulation temperature during sintering was 600℃. After sintering, it was naturally cooled, and then ground in a mortar for 5min to obtain a modified lithium iron manganese phosphate positive electrode material.
[0050] Example 2
[0051] A method for preparing a modified lithium manganese iron phosphate positive electrode material, the steps are as follows:
[0052] First, add 20 ml of anhydrous ethanol and 20 ml of deionized water into a ball mill, then weigh 0.01 mmol of ammonium dihydrogen phosphate, 0.01 mmol of lithium hydroxide, 0.01 mmol of manganese acetate and 0.01 mmol of ferric phosphate, and then weigh 10% of the total mass of citric acid as a carbon source, and 3% of the total mass of solid hexadecyltrimethylammonium bromide as a surfactant. Grind all the above solid raw materials evenly in a mortar and add them to a ball mill. Mill for 10 hours (the ball mill speed is 200 r / min, and the ball-to-material ratio is 10:1). Then, wash with deionized water and anhydrous ethanol three times each, and vacuum dry (dry at 80°C for 2 hours) to obtain a yellow lithium manganese iron phosphate precursor. The lithium iron manganese phosphate precursor was then placed in a quartz crucible and sintered at high temperature under the protection of a nitrogen atmosphere. The sintering cycle was 8 hours and the insulation temperature during sintering was 650°C. After sintering, it was naturally cooled and then ground in a mortar for 5 minutes to obtain a modified lithium iron manganese phosphate positive electrode material.
[0053] Example 3
[0054] A method for preparing a modified lithium manganese iron phosphate positive electrode material, the steps are as follows:
[0055] First, add 40 ml of deionized water into a ball mill, then weigh 0.01 mmol of diammonium hydrogen phosphate, 0.01 mmol of lithium chloride, 0.01 mmol of manganese trioxide and 0.01 mmol of ferric nitrate, and then weigh 10% of the total mass of dopamine hydrochloride of diammonium hydrogen phosphate, lithium chloride, manganese trioxide and ferric nitrate as a carbon source, and 3% of the total mass of dodecyltrimethylammonium chloride as a surfactant. Grind all the above solid raw materials evenly in a mortar and add them to a ball mill. Ball mill for 20 hours (the ball mill speed is 200 r / min, and the ball-to-material ratio is 10:1), then wash with anhydrous ethanol 3 times, and vacuum dry (dry at 80°C for 2 hours) to obtain a gray lithium manganese iron phosphate precursor. The lithium iron manganese phosphate precursor was then placed in a quartz crucible and sintered at high temperature under the protection of a nitrogen atmosphere. The sintering cycle was 10 hours and the insulation temperature during sintering was 700°C. After sintering, it was naturally cooled and then ground in a mortar for 5 minutes to obtain a modified lithium iron manganese phosphate positive electrode material.
[0056] Comparative Example 1
[0057] Same as Example 1, except that oleic acid is omitted.
[0058] Application Example 1
[0059] The preparation steps of lithium-ion batteries are as follows:
[0060] (1) Preparation of positive electrode for lithium-ion batteries
[0061] The modified lithium manganese iron phosphate positive electrode material prepared in Example 1 was mixed with conductive carbon powder and PVDF binder in a mass ratio of 80:10:10, and NMP (added amount was 1.5 ml / g) was added for homogenization to obtain an active material coating, which was then coated on an aluminum foil sheet (coating thickness was 10 μm), dried in an oven at 80°C, and then rolled with a double-roller machine, and then a positive electrode sheet with a diameter of 14 mm was obtained using a punching machine.
[0062] (2) Assembly of lithium-ion batteries
[0063] In a Universal (2440 / 750) inert gas glove box, a CR2025 button-type half-cell was assembled in the order of a negative electrode shell, a lithium sheet (as a negative electrode), an electrolyte (commercial LiPF6 electrolyte), a diaphragm (polypropylene diaphragm), an electrolyte (commercial LiPF6 electrolyte), a positive electrode sheet prepared in step (1), a gasket, a spring sheet, and a positive electrode shell.
[0064] Application Example 2
[0065] The same as Application Example 1, the only difference is that the modified lithium iron manganese phosphate positive electrode material prepared in Example 1 is replaced by the modified lithium iron manganese phosphate positive electrode material prepared in Example 2.
[0066] Application Example 3
[0067] The same as Application Example 1, except that the modified lithium iron manganese phosphate positive electrode material prepared in Example 1 is replaced by the modified lithium iron manganese phosphate positive electrode material prepared in Example 3.
[0068] Comparative application example 1
[0069] The same as Application Example 1, the only difference is that the modified lithium iron manganese phosphate positive electrode material prepared in Example 1 is replaced by the modified lithium iron manganese phosphate positive electrode material prepared in Comparative Example 1.
[0070] Test Example 1
[0071] Characterization of the morphology, structure and composition of lithium manganese iron phosphate
[0072] The modified lithium manganese iron phosphate positive electrode material prepared in Example 1 was characterized using Japan Rigaku Smartlab SE (X-ray powder diffractometer). The results are as follows: Figure 1 As shown, the XRD spectrum shows the characteristic peaks of lithium manganese iron phosphate and no impurity peaks, indicating that high-purity lithium manganese iron phosphate has been produced.
[0073] The lithium manganese iron phosphate positive electrode materials prepared in Example 1 and Comparative Example 1 were characterized using a Zeiss Sigma 300 field emission scanning electron microscope (SEM). Figure 2-3 As shown, Figure 2 is the SEM picture of Comparative Example 1, Figure 3 This is the SEM image of Example 1. It can be seen that the lithium manganese iron phosphate prepared in Example 1 has a spherical morphology with a particle size between 60-100 nm, and the particle agglomeration is significantly improved compared with the comparative example 1 in which no surfactant is added.
[0074] Figure 4 This is a surface scanning energy spectrum of the lithium manganese iron phosphate positive electrode material prepared in Example 1. It can be seen that the distribution of each element is relatively uniform.
[0075] Test Example 2
[0076] Battery performance test
[0077] The electrochemical performance of the CR2025 button half-cell prepared in Example 1-3 and Comparative Application Example 1 was tested using the Xinwei CT-4008 battery testing system. The voltage test range was 2.0-4.5V. The test results are shown in Figure 5 and Figure 6 .
[0078] Figure 5 The charge and discharge curves of the battery prepared by the modified lithium manganese iron phosphate of Example 1 at room temperature and 0.1C current are shown in Application Example 1. The charge capacity reaches 140.78 mAh / g, the discharge capacity reaches 139.6 mAh / g, and the efficiency is 99.17%. Figure 6 This is a cycle stability diagram of a battery prepared using the modified lithium manganese iron phosphate of Example 1 at room temperature and 0.1C current. After 100 cycles, the capacity retention rate of the modified lithium manganese iron phosphate battery is 97.16%.
[0079] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a modified lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: A phosphoric acid source, a manganese source, an iron source, a lithium source, a carbon source, a surfactant and a cosolvent are mixed, ball-milled, and vacuum-dried to obtain a lithium iron manganese phosphate precursor; the lithium iron manganese phosphate precursor is subjected to high-temperature sintering to obtain the modified lithium iron manganese phosphate positive electrode material; The surfactant is oleic acid, hexadecyltrimethylammonium bromide or dodecyltrimethylammonium chloride.
2. The method for preparing the modified lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The phosphate source is ammonium dihydrogen phosphate or diammonium hydrogen phosphate; the manganese source is manganese carbonate, manganese acetate, manganese phosphate, manganese trioxide or manganese tetraoxide; the lithium source is lithium acetate, lithium carbonate, lithium hydroxide or lithium chloride; the iron source is ferric phosphate, ferrous oxalate, ferric nitrate or ferric chloride.
3. The method for preparing the modified lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The carbon source is citric acid, ascorbic acid, glucose, sucrose, polyethylene glycol or dopamine hydrochloride.
4. The method for preparing the modified lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the phosphate source, manganese source, iron source and lithium source is 1:1:1:1; the amount of the carbon source is 10% of the sum of the mass of the phosphate source, manganese source, iron source and lithium source.
5. The method for preparing the modified lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: When the surfactant is oleic acid, the dosage ratio of the surfactant to the phosphoric acid source is 2ml:0.01mol; when the surfactant is hexadecyltrimethylammonium bromide or dodecyltrimethylammonium chloride, the dosage of the surfactant is 3% of the sum of the mass of the phosphoric acid source, manganese source, iron source and lithium source.
6. The method for preparing the modified lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The rotation speed of the ball mill is 200r / min, the ball-to-material ratio is 10:1, and the time is 10-20h; the temperature of the high-temperature sintering is 600-750°C, and the time is 6-10h.
7. A modified lithium manganese iron phosphate positive electrode material obtained by the preparation method according to any one of claims 1 to 6.
8. A positive electrode for a lithium ion battery, characterized in that: Including the modified lithium manganese iron phosphate positive electrode material as described in claim 7.
9. The method for preparing a positive electrode of a lithium ion battery according to claim 8, characterized in that: The following steps are involved: The modified lithium manganese iron phosphate positive electrode material is mixed with conductive carbon black and a binder, and then NMP is added for homogenization to obtain an active material coating; the active material coating is coated on a substrate, dried and then rolled to obtain the lithium ion battery positive electrode.
10. A lithium ion battery, characterized in that: The lithium ion battery positive electrode according to claim 8 is used as the positive electrode.
Citation Information
Patent Citations
Preparation method of high-density lithium iron phosphate cathode material
CN108529584A
Composite bimetal boride for alkaline aqueous solution electrolyte system battery positive-electrode material and preparation method of composite bimetal boride
CN109850912A
Lithium iron phosphate positive electrode material and preparation method thereof
CN109888282A
Preparation method of lithium manganese iron phosphate positive electrode material
CN113929073A
Composite lithium manganese iron phosphate material as well as preparation method and application thereof
CN115832258A
